MEMAHAMI THIRD WORLD APPROACHES TO INTERNATIONAL LAW ( TWAIL ) - Dyah R. A. Daties (SASI, 2017)
The development of international law can not be separated from the history of the world, butthe development can not be separated also from the dark width with the outbreak of WorldWar I and World War II. After the end of World War II, the beginning of a period ofbrightness which is a new stage for the development of society and international law. Thereare some new changes and developments but the situation does not reflect the world as awhole because of the polarization of the world or the international community at that timewas divided into two. The second group, which is the former colony of the former, considersthat international law is heavily dominated by European and American values, and in no wayaccommodates the values of local wisdom from the former colonies. Along with thedevelopment of contemporary international law, the "lawsuit" of former colonies that areusually also referred to as third world countries against the domination of European andAmerican countries in international law is the reason for the birth of Third World Approachesto International Law. TWAIL exists to solve, appearing to show the material and ethicalissues and difficulties facing the Third World.